Proverbs and the African tree of life : grafting Biblical proverbs on to Ghanaian Eve folk proverbs - Akoto-Abutiate, Dorothy B. E. A. (Studies in Systematic Theology, 2014)
In Proverbs and the African Tree of Life Dorothy BEA Akoto-Abutiate juxtaposes chosen sayings from Proverbs and selected Ewe Folk proverbs using the agricultural metaphor of "grafting," which she calls a "hermeneutic of grafting." Though these two sets of sayings come from completely different cultural contexts, Akoto argues that folk sayings/proverbs, which abound in Africa, should be considered as an already mature, established tree on to which a piece of the biblical tree is spliced or engrafted to produce hybridized fruits that have uniquely different tastes than the fruits of each tree individually. This metaphorical grafting process allows the message of the Bible (in Proverbs) to be understood, imbibed and appropriated in Africa.